2005
DOI: 10.1289/ehp.8072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Detrimental Effects of Environmental Contaminants on Growth and Reproductive Physiology of White Sturgeon in Impounded Areas of the Columbia River

Abstract: This study sought to determine whether wild white sturgeon from the Columbia River (Oregon) were exhibiting signs of reproductive endocrine disruption. Fish were sampled in the free-flowing portion of the river (where the population is experiencing reproductive success) and from three reservoirs behind hydroelectric dams (where fish have reduced reproductive success). All of the 18 pesticides and almost all of the 28 polychlorinated biphenyls (PCBs) that were analyzed in livers and gonads were detected in at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 31 publications
7
65
2
Order By: Relevance
“…Feist et al (2005) found that Lower Columbia River white sturgeon tissues (liver and gonads) contained significant levels of OC pesticides, particularly p,p 0 -dichlorodiphenyldichloroethylene (DDE). The data from this study indicate that OC contaminants may have deleterious effects on growth and reproduction in white sturgeon, particularly fish collected from the impounded sections of the Lower Columbia River.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Feist et al (2005) found that Lower Columbia River white sturgeon tissues (liver and gonads) contained significant levels of OC pesticides, particularly p,p 0 -dichlorodiphenyldichloroethylene (DDE). The data from this study indicate that OC contaminants may have deleterious effects on growth and reproduction in white sturgeon, particularly fish collected from the impounded sections of the Lower Columbia River.…”
mentioning
confidence: 99%
“…The objectives of this study were to measure OC pesticide concentrations in blood plasma samples of juvenile white sturgeon collected from 4 sites on the Lower Columbia River and assess the relationship between OC levels in plasma and in corresponding tissues (gonad and liver) from fish that were analyzed as part of a previous study conducted by our research group (Feist et al 2005). We also looked at the relationship between plasma OC levels and plasma sex steroids that were previously measured in corresponding fish (Feist et al 2005) to evaluate the effectiveness of utilizing blood plasma as a non-destructive means for monitoring OC contaminants in Columbia River white sturgeon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the present study did not reveal morphometric differences in gonadal condition of Largescale Sucker that could be associated with gradients of exposure to organic contaminants or other environmental factors (i.e., temperature) in the lower Columbia River (see also later discussion). The lack of association between morphometric indices of gonadal condition and the downstream increase in liver organic contaminant concentrations of Largescale Sucker is noteworthy because other field studies with species such as White Sturgeon (Acipenser transmontanus) (Feist et al, 2005), European Chub (Leuciscus cephalus) (Randak et al, 2009) and English Sole (Parophrys vetulus) (Sol et al, 2008) have reported negative correlations between tissue (in some cases including liver) organic contaminants, and morphometric gonadal indices such as GSI. As noted already, GSI measurements must be interpreted with caution, especially if collected near or during spawning periods.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the specific use of ALP, Ca, Zn and Mg, instead of VTG, was incorporated into this study in order to determine the feasibility of using these relatively simple and cost-effective endpoints to identify DDT induced responses. In terms of identifying higher level responses, the changes in the catfish gonad and body were assessed, using the gonad somatic index (GSI), analysis of co-variance (ANCOVA) adjusted gonads and condition factor (CF) (Fiest et al, 2005;Sepuveda et al, 2003;Sheahan et al, 2002). The former two are both indicative of gonad condition.…”
Section: Introductionmentioning
confidence: 99%